2012
DOI: 10.1002/pd.4008
|View full text |Cite
|
Sign up to set email alerts
|

What do French patients and geneticists think about prenatal and preimplantation diagnoses in Marfan syndrome?

Abstract: This study showed that the majority of patients were in favour of PND and that opinions among practitioners varied widely, but that overall, practitioners favoured a systematic multidisciplinary evaluation of the couple's request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
2
2
1
1
Order By: Relevance
“…Musculoskeletal tissues are some of the most obviously involved tissues in Marfan syndrome but these manifestations are often age dependent. Some musculoskeletal abnormalities, in fact, are absent or less evident during the skeletal growth and we agree with Dean [5] and with Coron et al [23] that the Ghent criteria are unreliable for children. In fact, as described in the revised Ghent criteria [4], clinical decision can be difficult in children.…”
Section: Discussionsupporting
confidence: 91%
“…Musculoskeletal tissues are some of the most obviously involved tissues in Marfan syndrome but these manifestations are often age dependent. Some musculoskeletal abnormalities, in fact, are absent or less evident during the skeletal growth and we agree with Dean [5] and with Coron et al [23] that the Ghent criteria are unreliable for children. In fact, as described in the revised Ghent criteria [4], clinical decision can be difficult in children.…”
Section: Discussionsupporting
confidence: 91%
“…Disease severity was not associated with demand for prenatal diagnosis (Farhi et al 2008), a finding similar to this study. Findings are also comparable to a recent study of Marfan disease, a disorder also characterized by phenotypic variability, in which the majority of participants were in favor of prenatal diagnosis (Coron et al 2012). Of those participants who had affected children, similar to previous studies we found that mothers worried how the disease will progress (Hummelvoll and Antonsen 2013).…”
Section: Inheritancesupporting
confidence: 89%
“…One of the more difficult debates by critics and family members of affected individuals has been the argument that selecting embryos without mutations diminishes the importance of people disabled by the diseases. 25,61,62 However, for most couples, the choice to proceed with PGD is not driven by these notions. Several studies have demonstrated that the decision to proceed with PGD is quite complex, encompassing many considerations, 63 with the consensus that most proceed with PGD to protect their future children against the suffering they witness in other family members.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Several studies have demonstrated that the decision to proceed with PGD is quite complex, encompassing many considerations, 63 with the consensus that most proceed with PGD to protect their future children against the suffering they witness in other family members. 30,31,40,62 Critics have also warned against PGD practice moving toward a "designer child," likely stemming from ability to use PGD for variable penetrance and cancer predisposing genes and particularly with the prospect of comprehensive embryo testing. 34,38,64 Ethical obligations of the physician have been examined with concerns about providing a plethora of complicated genetic information to patients and about the uncertainty regarding on whom the responsibility befalls to select the optimal embryo.…”
Section: Ethical Considerationsmentioning
confidence: 99%